Patellar tendon properties distinguish elite from non-elite soccer players and are related to peak horizontal but not vertical power - Murtagh, C. F.; Stubbs, M.; Vanrenterghem, J.; O`Boyle, A.; Morgans, R.; Drust, B.; Erskine, R. M. (European Journal of Applied Physiology, 2018)
Purpose: To investigate potential differences in patellar tendon properties between elite and non-elite soccer players, and to establish whether tendon properties were related to power assessed during unilateral jumps performed in different directions. Methods: Elite (n = 16; age 18.1 ± 1.0 years) and non-elite (n = 13; age 22.3 ± 2.7 years) soccer players performed vertical, horizontal-forward and medial unilateral countermovement jumps (CMJs) on a force plate. Patellar tendon (PT) cross-sectional area, elongation, strain, stiffness, and Young`s modulus (measured at the highest common force interval) were assessed with ultrasonography and isokinetic dynamometry. Results: Elite demonstrated greater PT elongation (6.83 ± 1.87 vs. 4.92 ± 1.88 mm, P = 0.011) and strain (11.73 ± 3.25 vs. 8.38 ± 3.06%, P = 0.009) than non-elite soccer players. Projectile range and peak horizontal power during horizontal-forward CMJ correlated positively with tendon elongation (r = 0.657 and 0.693, P < 0.001) but inversely with Young`s modulus (r = - 0.376 and - 0.402; P = 0.044 and 0.031). Peak medial power during medial CMJ correlated positively with tendon elongation (r = 0.658, P < 0.001) but inversely with tendon stiffness (r = - 0.368, P = 0.050). Conclusions: Not only does a more compliant patellar tendon appear to be an indicator of elite soccer playing status but it may also facilitate unilateral horizontal-forward and medial, but not vertical CMJ performance. These findings should be considered when prescribing talent selection and development protocols related to direction-specific power in elite soccer players.